Bomba atômica: ensinando física e energia nuclear num contexto histórico e sociocultural - Souza, Marcos Vinicius Lima (2016)
The Modern and Contemporary Physics is present in our lives, permeating the technology we use and adjusting social and cultural habits, but it is still sidelined most of the high schools. Aiming to work some concepts of Physics and Nuclear Power, elaborated and applied a Didactic Sequence that brings the theme generator the Atomic Bomb according to Freire's pedagogy and the Three Pedagogical Moments proposed by Deilizocov and Angotti. Throughout the meetings, use the History and Philosophy of Science and science approach, Technology, Society and Environment to teach physical concepts as well as to discuss military and ethical aspects of the production of such weapons and use of its technology for nuclear energy. Political, social and ethical issues underlying the construction of such a nuclear weapon were discussed, aimed at civic education and a more effective learning for students and beneficial to society. The participation of students during class was higher compared to classes before the implementation of didactic sequence, and demonstrated a good understanding of the contents worked on this proposal